2011
DOI: 10.1074/jbc.m111.231316
|View full text |Cite
|
Sign up to set email alerts
|

The Acylation State of Surface Lipoproteins of Mollicute Acholeplasma laidlawii

Abstract: Acylation of the N-terminal Cys residue is an essential, ubiquitous, and uniquely bacterial posttranslational modification that allows anchoring of proteins to the lipid membrane. In Gram-negative bacteria, acylation proceeds through three sequential steps requiring lipoprotein diacylglyceryltransferase, lipoprotein signal peptidase, and finally lipoprotein N-acyltransferase. The apparent lack of genes coding for recognizable homologs of lipoprotein N-acyltransferase in Gram-positive bacteria and Mollicutes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…It has been suggested earlier the Mollicutes are characterized by diacylation (45). However, we determined that A. laidlawii has three acyl residues (50).…”
Section: General Genomic Featuresmentioning
confidence: 45%
“…It has been suggested earlier the Mollicutes are characterized by diacylation (45). However, we determined that A. laidlawii has three acyl residues (50).…”
Section: General Genomic Featuresmentioning
confidence: 45%
“…The enzymes Lgt and Lsp are conserved in all classes of bacteria, whereas Lnt is only present in Proteobacteria, Actinobacteria, and Spirochetes (56,60,63). Recent reports, however, demonstrated that triacylated lipoproteins exist at least in the Staphylococcus species of Gram-positive bacteria (32) and in Mollicutes (50). This suggests that they might also possess N-acyltransferase activity.…”
mentioning
confidence: 92%
“…To prepare lipopeptides for MS analysis, the strategy of Serebryakova et al was utilized, with minor modifications (57). After SDS-PAGE separation (described above for immunoblotting), purified Lpp(K58A)-Strep-tag and enriched lipoproteins from E. faecalis and B. cereus were transferred onto BioTract NT nitrocellulose transfer membrane (PALL Life Sciences) and stained with Ponceau S (0.2% in 5% acetic acid).…”
Section: Methodsmentioning
confidence: 99%